System rachunku kosztów działań w obszarze IT na przykładzie instytucji finansowej - Kowalczyk, Mirosław (Activity Based Costing System in IT Area Exampled on Financial Institution, 2006)
The aim of this paper is to present issues concerning Activity Based Costing. The Harvard economists R. Cooper and R.S. Kaplan popularized Activity Based Costing (ABC) through their article "Measure Cost Right: Make the Right Decisions" published in Harvard Business Review in 1988. ABC generates more accurate cost and performance information related to specific products, services, customers (cost objects) than it is available to managers through traditional cost accounting approaches. ABC is a more effective method of assigning the cost of activities to products (IT systems), services (IT services) and customers (service recipients) in IT area of financial institution.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 194-204